2014
DOI: 10.1044/2014_jslhr-l-13-0176
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Sensitivity to Long-Distance Dependencies in Children With a History of Specific Language Impairment: Electrophysiological Evidence

Abstract: Purpose One possible source of tense and agreement limitations in children with SLI is a weakness in appreciating structural dependencies that occur in many sentences in the input. We tested this possibility in the present study. Method Children with a history of SLI (H-SLI; N = 12; M age 9;7) and typically developing same-age peers (TD; N = 12; M age 9;7) listened to and made grammaticality judgments about grammatical and ungrammatical sentences involving either a local agreement error (e.g., Every night th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…Earlier we noted that a recent study by Purdy et al (in press) lends support to this interpretation. Children with a history of a protracted period of tense/agreement inconsistency exhibited event-related potentials (ERPs) indicating that they were successfully detecting local errors (e.g.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Earlier we noted that a recent study by Purdy et al (in press) lends support to this interpretation. Children with a history of a protracted period of tense/agreement inconsistency exhibited event-related potentials (ERPs) indicating that they were successfully detecting local errors (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…This expectation seems especially plausible given a recent study by Purdy, Leonard, Weber-Fox, and Kaganovich (in press). These investigators found that children with a history of SLI, including inconsistent use of tense/agreement morphology, had a tendency to treat sentences such as We watch the happy girl climbs up the ladder as acceptable, as measured both behaviorally and through electrophysiological measures.…”
Section: Introductionmentioning
confidence: 96%
“…Leonard and Deevy (2011) and Purdy, Leonard, Weber-Fox, and Kaganovich (in press) provide comprehension data consistent with this interpretation, and Leonard and Deevy also give examples of how this same assumption can lead to well documented word order errors in languages such as German and Swedish. As can be seen, the protracted period of children with SLI making errors such Him hold the worm and She eating my candy has enabled investigators to propose specific hypotheses about the nature of inappropriate input extraction.…”
Section: Sli and Language Inputmentioning
confidence: 61%
“…Friedmann & Novogrodsky, 2004;Montgomery & Evans, 2009;van der Lely, Jones, & Marshall, 2011). An investigation by Purdy and colleagues tested the influence of sentence complexity on listening comprehension in a direct way (Purdy et al, 2014). School-age children with and without SLI were asked to make grammatical judgments of verb agreement and finiteness errors in one-clause (simple) sentences (e.g., every night they talks on the phone) versus two-clause (complex) object complement sentences (he makes the quiet boy talks a little louder).…”
Section: Comprehension Studiesmentioning
confidence: 99%
“…A number of grammatical features contribute to sentence complexity; these include embedding/ subordination, word order variations, and long-distance dependencies as found in wh-object questions or object relative clauses (Thompson & Shapiro, 2007). In comparison with age peers, there is considerable evidence that school-age children and adolescents with SLI find complex sentences more difficult to comprehend and produce (Fey, Catts, Proctor-Williams, Tomblin, & Zhang, 2004;Gillam & Johnston, 1992;Marinellie, 2004;Montgomery & Evans, 2009;Nippold, Mansfield, Billow, & Tomblin, 2008Purdy, Leonard, Weber-Fox, & Kaganovich, 2014;Scott & Windsor, 2000). In this article, we are concerned with the first type of complexity: sentences with two clauses-one main clause and one subordinate clause.…”
mentioning
confidence: 99%